Revitalizing Sodetan Sekretaris River as a View for Centro City Residence and Its Surroundings - Angela Subagio; Siwi Samsu Hendra (Fakultas Teknik Universitas Pancasila, 2025)
Many apartments offer various advantages, one of which is the view. However, not the case with Centro City Residence apartment located on Jalan DaanMogot. Problems arise in the room units facing Kali Sodetan Sekretaris due to the poor ventilation and unpleasant views. Rather than providing fresh air, the window allows unpleasant odors from the river to enter the rooms. Moreover, the view consists of a heavily polluted river, filled with garbage and dark, murky water. This research, conducted using a descriptive qualitative method, aims to explore the role of architectural design in proposing alternative solutions that benefit both the residents of Centro City Residence and the surrounding. Some solutions that can be done are to revive Sodetan Sekretaris river as a tourist spot for the surrounding. By making it a tourist spot and is expected to be free from garbage. This includes transforming the riverfront into a clean, inviting space with pedestrian walkways, seating areas, photo spots, and street lighting to attract local visitors and encourage community engagement.